THE CONTRIBUTION OF YARD UTILIZATION TO HOUSEHOLD FOOD REVENUE AND EXPENDITURE IN DEWANTARA SUBDISTRICT, ACEH UTARA - Martina, Martina; Praza, Riyandhi; Zuriani, Zuriani (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
The use of yard land is carried out to maximize the use of land as a medium for planting commodities that can be used to meet the food needs of the community in Dewantara Sub-Sub-District. Commodities that are cultivated in the yard are horticultural commodities in the form of vegetables, spices, fruits and ornamental plants. Through the use of the yard, households can increase their revenue and save on food expenditure. This study aims to analyze the contribution of yard use to household food revenue and expenditure in Dewantara Sub-Sub-District, Aceh Utara. The research sample was 60 families who used the yard with horticultural cultivation which was determined by simple random sampling. The types of data used are primary data and secondary data. Data were analyzed using quantitative descriptive analysis. The results showed that the use of yards with horticultural cultivation in Dewantara Sub-Sub-District contributed to an increase in household food revenue and expenditure. The average revenue earned by households through the use of yards is 50,045.35 IDR/month. The contribution to the increase in revenue is 1.1% and the contribution to food expenditure is 2.56%. The contribution given from the use of the yard is low, but the use of the yard is very meaningful in meeting household food needs. Households should use the yard optimally, be more innovative, and be carried out sustainably.